A Genome-Wide Analysis of StTGA Genes Reveals the Critical Role in Enhanced Bacterial Wilt Tolerance in Potato During Ralstonia solanacearum Infection - Tian, Tian; Yu, Ruimin; Suo, Yanyun; Cheng, Lixiang; Li, Guizhi; Yao, Dan; Song, Yanjie; Wang, Huanjun; Li, Xinyu; Gao, Gang (Frontiers in Genetics, 2022)
TGA is one of the member of TGACG sequence-specific binding protein family, which plays a crucial role in the regulated course of hormone synthesis as a stress responsive transcription factor (TF). Little is known, however, about its implication in response to bacterial wilt disease in potato (Solanum tuberosum) caused by Ralstonia solanacearum. Here, we performed an in silico identification and analysis of the members of TGA family based on the whole genome data of potato. In total, 42 StTGAs were predicted to be distributed on 4 chromosomes in potato genome. Phylogenetic analysis showed that the proteins of StTGAs could be divided into 6 sub-families. We found that many of these genes have more than one exon according to the conserved motif and gene structure analysis. The heat map inferred that StTGAs are generally expressed in different tissues which are at different stages of development. Genomic collinear analysis showed that there are homologous relationships among potato, tomato, pepper, Arabidopsis and tobacco TGA genes. Cis-element in silico analysis predicted that there may be many cis-acting elements related to abiotic and biotic stress upstream of StTGAs promoter including plant hormone response elements. A representative member StTGA39 was selected to investigate the potential function of the StTGA genes for further analysis. Quantitative real-time polymerase chain reaction (qRT-PCR) assays indicated that the expression of the StTGAs were significantly induced by R. solanacearum infection and up-regulated by exogenous salicylic acid (SA), abscisic acid (ABA), gibberellin 3(GA3) and methyl jasmonate (MeJA). The results of yeast one-hybrid (Y1H) assay showed that StTGA39 regulates S. tuberosum BRI1-associated receptor kinase 1 (StBAK1) expression. Thus, our study provides a theoretical basis for further research of the molecular mechanism of the StTGA gene of potato tolerance to bacterial wilt.